Penerapan Algoritma Fuzzy Possibilistic C-Means (FPCM) pada Pengelompokan Kabupaten/Kota di Indonesia Berdasarkan Indikator Indeks Pembangunan Manusia Tahun 2022 - Ghia Fauziah Aghyari; Abdul Kudus (Bandung Conference Series: Statistics, 2023)
Abstract. Human resources are a crucial factor in human development and a key component in achieving prosperity in every country. The success of development is measured in various ways, one of the most popular being the calculation of the Human Development Index (HDI). The classification of districts and cities in Indonesia is necessary as a reference for government program planning and evaluation to enhance human development in those areas. Partitioning clustering is one of the clustering techniques that aims to partition data into several groups or partitions, with the number of groups usually predetermined. One of the algorithms used in partitioning clustering is Fuzzy Possibilistic C-Means (FPCM). Fuzzy Possibilistic C-Means (FPCM) is an extension of two algorithms, namely Fuzzy C-Means (FCM) and Possibilistic C-Means (PCM). FPCM combines fuzzy and possibilistic concepts to address the weaknesses of the previous algorithms. Therefore, the Fuzzy Possibilistic C-Means (FPCM) algorithm is applied to cluster the districts and cities in Indonesia based on the indicators of the Human Development Index. Based on the results of the Modified Partition Coefficient (MPC) index, the optimal number of clusters is determined to be four clusters. Cluster 1 contains 146 districts and cities, cluster 2 contains 97 districts and cities, cluster 3 contains 141 districts and cities, and cluster 4 contains 130 districts and cities. Abstrak. Sumber daya manusia adalah faktor penting dalam pembangunan manusia yang menjadi komponen utama dalam mencapai kemakmuran di setiap negara. Keberhasilan pembangunan diukur dengan berbagai cara, salah satunya yang paling populer melalui perhitungan Indeks Pembangunan Manusia (IPM) atau Human Development Index (HDI). Pengelompokan wilayah Kabupaten/Kota di Indonesia perlu dilakukan sebagai acuan dalam perencanaan dan evaluasi program pemerintah untuk meningkatkan pembangunan manusia di daerah tersebut. Partitioning clustering adalah salah satu teknik pengelompokan yang mencoba mempartisi data ke dalam beberapa kelompok (partition) dan jumlah kelompok yang akan dibuat biasanya telah ditentukan sebelumnya dan salah satu algoritma pada partitioning clustering adalah Fuzzy Possibilistic C-Means (FPCM). Algoritma Fuzzy Possibilistic C-Means (FPCM) yang merupakan perluasan dari dua algoritma yaitu algoritma Fuzzy C-Means (FCM) dan Possibilistic C-Means (PCM). Fuzzy Possibilistic C-Means (FPCM) menggabungkan konsep fuzzy dan possibilistic untuk mengurangi kelemahan dari algoritma sebelumnya. Oleh karena itu diterapkan algoritma Fuzzy Possibilistic C-Means (FPCM) untuk mengelompokan Kabupaten/Kota di Indonesia berdasarkan indikator indeks pembangunan manusia. Berdasarkan hasil indeks Modified Partition Coefficient (MPC) jumlah klaster yang optimal adalah empat klaster. Pada klaster 1 berisi 146 Kabupaten/Kota, klaster 2 berisi 97 Kabupaten/Kota, klaster 3 berisi 141 Kabupaten/Kota, dan klaster 4 berisi 130 Kabupaten/Kota.